Classification of white blood cells by deep learning methods for diagnosing disease - Yildirim, Muhammed; Çinar, Ahmet (International Information and Engineering Technology Association, 2019)
Leukocytes, also known as white blood cells, are a group of cells that protect the body against infections, which is an important part of the immune system. The classification of white blood cells is widely used to diagnose various diseases, such as AIDS, leukemia, myeloma and anemia. However, the conventional methods to classify white blood cells are time consuming and prone to errors. In this paper, one of the most popular neural networks, convolutional neural network (CNN) is selected to differentiate between different types of white blood cells, namely, eosinophil, lymphocyte, monocyte and neutrophil. The CNN was coupled with Alexnet, Resnet50, Densenet201 and GoogleNet in turn, and trained with the Kaggle Dataset. Then, Gaussian and median filters were applied separately to the images in the database. The new images were classified again by the CNN with each of the four networks. The results obtained after applying the two filters to the images were better than the results obtained with the original data. The research results make it easier to diagnose blood related diseases. © 2019 Mattingley Publishing. All rights reserved.
Keywords: Cells; Cytology; Deep learning; Diagnosis; Median filters; Neural networks; Conventional methods; Convolutional neural network; Gaussians; Group of cells; Learning methods; Research results; White blood cells; Blood